Localized surface plasmon-enhanced green quantum dot light-emitting diodes using gold nanoparticles. Issue 25 (21st March 2015) - Kim, Na-Yeong; Hong, Sang-Hyun; Kang, Jang-Won; Myoung, NoSoung; Yim, Sang-Youp; Jung, Suhyun; Lee, Kwanghee; Tu, Charles W.; Park, Seong-Ju
<x xml:space="preserve">Abstract</x> We demonstrate solution processed gold nanoparticles and a ZnO hybrid structure for localized surface plasmon-enhanced colloidal quantum-dot light-emitting diodes.